PENGARUH DISIPLIN KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA PUSKESMAS KALANGANYAR - Muhi Mukti (E-Journal Studia Manajemen, 2023)
Human resources have always been the main asset for companies so that they can continue to develop. By having quality human resources, companies will be better able to develop their business activities. This research is included in quantitative research. The conclusion of this research is that there is no influence of the Work Discipline variable on Employee Performance at the Kalanganyar Community Health Center, there is an influence of the Leadership Style variable on Employee Performance at the Kalanganyar Community Health Center. and There is an influence of Work Discipline and Leadership Style variables on employee performance at the Kalanganyar Community Health Center.